The Role Of Community Empowerment In Improving The Welfare Of Farming Households In Nagari Kampung Pinang, Lubuk Basung District, Agam Regency, West Sumatra Province - Firman, Pandi; Irwan, Irwan; Elvawati, Elvawati (International Journal of Education, Vocational and Social Science, 2025)
Agriculture plays a strategic role in the Indonesian economy, particularly in West Sumatra, where the majority of the population relies on rice cultivation for their livelihood. This study aims to analyze the role of farmer group empowerment in improving the welfare of farming households in Nagari Kampung Pinang, Lubuk Basung District, Agam Regency. The study employed a mixed methods approach. Data collection methods included document study, observation, in-depth interviews, questionnaires, and focus group discussions (FGDs). The research location was in Kampung Pinang Village, Lubuk Basung District, Agam Regency. Qualitatively, the research used the Milles and Huberman (1992) model, which begins with data collection, data reduction, data presentation, and drawing conclusions. Quantitatively, the research used MACTOR software analysis to evaluate the relationships and influences between factors. The theory used in this research is the Actor theory put forward by Macaulay and Cook (1996). The research results show that farmer groups play a strategic role as a liaison for access to production facilities, a forum for knowledge and technology transfer, a social actor that strengthens solidarity, a market mediator, a production supervisor, and a facilitator of cross-sector partnerships. MACTOR analysis revealed that the most intense interaction occurs between farmer groups and field agricultural extension workers, while private sector involvement is still limited. Structured, participatory, and collaborative empowerment programs have increased member capacity and agricultural productivity, which has had a positive impact on the welfare of farming households. These findings emphasize the importance of strengthening coordination between actors, developing partnerships with the private sector, and increasing the institutional capacity of farmer groups to ensure the sustainability of local agricultural development.